Intelligence, age and schooling: data from the Battery of Reasoning Tests (BRT-5) - Primi,Ricardo (2012)
Intelligence is commonly divided into two distinctive areas: fluid intelligence (Gf), which is understood as the skill of reasoning or intelligence as a process, and crystallized intelligence (Gc) that involves skills that are more related to learning and experience (knowledge-based skills). The objective of the present work was to investigate the effects that schooling and age exert on fluid and crystallized intelligence measuring students' results in sub-tests of the Battery of Reasoning Test (BRT-5). This study considered a sample composed of 1,722 students - 603 were assessed with Form A of the battery and 1,119 with Form B. The results show that intelligence is systematically associated with schooling and age. Some difficulties in separating the effects of cognitive development from the effects of formal learning on students' cognitive performance are also emphasized.